IMPLEMENTATION OF MULTICULTURAL EDUCATIONAL VALUES IN MADRASAH - Samsudin, Samsudin; Ningsih, Tutuk (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
Multicultural values are an important part that must be taught to students, this is because Indonesia has a diversity of religions, ethnicities, cultures, and customs. The purpose of this study is to analyze the implementation of multicultural educational values in Madrasas. This research was conducted at Madrasah Ibtidaiyah Ma'arif NU Sunyalangu Kebumen, the object of this research is the values of multicultural education implemented in schools, and the subjects in this study are teachers and students. This study uses a qualitative method with a naturalistic approach (naturalistic inquiry). Data collection was carried out by observation, interview, and documentation techniques. Data analysis is carried out with the Miles & Huberman interactive model, starting from the data reduction process, data presentation, verification and conclusion drawing. The results of the study show that the values of multicultural education at Madrasah Ibtidaiyah Ma'arif NU Sunyalangu Kebumen have been well implemented through extracurricular and intracurricular activities. The extracurricular activities carried out include scouting, paskibra, sports, arts, and PMR activities. The intracurricular activities carried out are Islamic Religious Lessons, general lessons, flag ceremonies, and congregational prayers and recitations. The multicultural values that appear in children are tolerance, cooperation, harmony, togetherness, nationalism, solidarity, and social.